2009
DOI: 10.1111/j.1740-0929.2008.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient utilization and manure P excretion in growing pigs fed corn‐barley‐soybean based diets supplemented with microbial phytase

Abstract: The effect of high levels of microbial phytase supplementation in diets for growing pigs was studied in a 2-week performance and nutrient digestibility trial involving 28 growing pigs weighing 16.4 +/- 1.06 (mean +/- SD) kg. Seven corn-barley-soybean meal-based diets consisting of a positive control (PC) formulated to meet or exceed NRC nutrient requirements; a negative control (NC) with non-phytate P reduced by 0.1% unit from NRC requirement and fed without or with 500 or 1000 U/kg; a doubled negative control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
4
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
1
17
4
3
Order By: Relevance
“…Feeding the enzyme phytase enables utilization of plant source P by pigs and allows diets containing reduced amounts of inorganic P to be nutritionally adequate. Based on previous reports (Veum et al, 2006;Veum and Ellersieck, 2008;Emiola et al, 2009), MCP was excluded from diets containing phytase unless the total P provided by the final diet (g of total P/kJ of NE) was not ≥100% of the available P presented by the reference diets.…”
Section: Diet Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Feeding the enzyme phytase enables utilization of plant source P by pigs and allows diets containing reduced amounts of inorganic P to be nutritionally adequate. Based on previous reports (Veum et al, 2006;Veum and Ellersieck, 2008;Emiola et al, 2009), MCP was excluded from diets containing phytase unless the total P provided by the final diet (g of total P/kJ of NE) was not ≥100% of the available P presented by the reference diets.…”
Section: Diet Formulationmentioning
confidence: 99%
“…Inclusion of phytase in pig diets enables diets with less total P to be nutritionally adequate and may reduce P excretion by pigs (Veum et al, 2006;Veum and Ellersieck, 2008;Emiola et al, 2009). Because MCP requires a large amount of nonsolar energy to produce, its near elimination from diet formulations greatly reduces nonsolar energy inputs for complete diet production.…”
mentioning
confidence: 99%
“…Hence, fecal and urine P excreted by the animals are presented and discussed in terms of their concentrations rather than the quantity produced. Animal performance data for this study has been reported elsewhere (Emiola et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Microbial phytase increases the apparent total tract digestibility of phosphorus (P) in pigs, but only to a maximum of about 44% to 59% in maize-soybean meal (SBM)-based diets fed low inorganic P addition (Brana et al, 2006;Emiola et al, 2009;Kerr et al, 2010). Thus, there is an increased focus on maximization of the efficacy of phytase to improve P digestibility further by 'pre-digestion' methods (soaking, fermentation) (Pedersen and Stein, 2010;Blaabjerg et al, 2010a) and feed processing (grinding, pelleting, heat treatment) (Oryschak et al, 2002;Pedersen and Stein, 2010;Blaabjerg et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%